Ngô Quốc Anh

June 5, 2011

Variation of the determinant

Filed under: Riemannian geometry — Ngô Quốc Anh @ 6:05

Today, we shall prove the following identity

\displaystyle\boxed{\delta \det(g) = \delta \det (g_{\mu\nu}) = \det(g )g^{\mu\nu} \delta g_{\mu\nu} }.

First, by the Jacobi formula, we know that for any matrix A

\displaystyle d\mbox{det} (A) = \mbox{tr} (\mbox{adj}(A) \, dA)

where d is a differential of A. Since

\displaystyle A^{-1}=\frac{1}{\det (A)}\mbox{adj}(A),

we can rewrite the Jacobi formula as follows

\displaystyle d\mbox{det} (A) = \det (A)\mbox{tr} (A^{-1}dA).

We now make use this rule with A replaced by metric g and d replaced by \delta. Obviously,

\displaystyle \delta \det(g) =\det(g)\mbox{tr}(g^{-1}\delta g)= \det(g )g^{\mu\nu} \delta g_{\mu\nu}

where we have used the fact that g^{-1}=g^{\mu\nu} and that

\displaystyle \mbox{tr}(AB)=\sum_{i,j}A_{ij}B_{ij}.


Create a free website or blog at